Tingkat Pendidikan sebagai Determinan Masalah Kesehatan Mental Remaja - Gitari, Ni Made; Sarniyati, Maria Yeni (Jurnal Penelitian Kesehatan SUARA FORIKES, 2024)
Adolescents are a group that is vulnerable to mental health problems. Mental health problems in adolescents in the Colol Health Center work area have not been studied thoroughly due to limited resources. This study aimed to analyze the correlation between gender and education level with adolescent mental health in the Colol Health Center work area, East Manggarai Regency. This study was conducted with a cross-sectional design in seven junior high schools and one senior high school in the Colol Health Center work area. Four hundred and seventy-eight adolescents aged 12-18 years were selected through consecutive sampling techniques. Data were collected by filling out a questionnaire, namely the strengths and difficulties questionnaire (SDQ) to measure the mental health status of the subjects, and also a questionnaire to collect data on education and gender. Data were analyzed using the Chi-square test. The results showed that the most common mental health problems found were emotional problems (27.0%) and behavioral problems (24.5%). There was no relationship between gender and mental health, but there was a relationship between the respondent's education level with emotional problems (p = 0.001) and total difficulties (p = 0.002). It could be concluded that mental health in adolescents in the Colol Health Center work area is related to their level of education.Keywords: adolescents; mental health problems; level of education ABSTRAK Remaja merupakan kelompok yang rentan terhadap masalah kesehatan mental. Masalah kesehatan mental pada remaja di wilayah kerja Puskesmas Colol belum diteliti secara menyeluruh karena keterbatasan sumber daya. Penelitian ini bertujuan untuk menganalisis korelasi antara jenis kelamin dan tingkat pendidikan dengan kesehatan mental remaja di wilayah kerja Puskesmas Colol, Kabupaten Manggarai Timur. Penelitian ini dilaksanakan dengan desain cross-sectional di tujuh sekolah menengah pertama dan satu sekolah menengah atas di wilayah kerja Puskesmas Colol. Empat ratus tujuh puluh delapan remaja berusia 12-18 tahun dipilih melalui teknik consecutive sampling. Data dikumpulkan melalui pengisian kuesioner yakni strengths and difficulties questionnaire (SDQ) untuk mengukur status kesehatan mental subjek, dan juga kuesioner untuk mengumpulkan data pendidikan dan jenis kelamin. Data dianalisis menggunakan uji Chi-square. Hasil penelitian menunjukkan bahwa masalah kesehatan mental yang paling umum ditemukan adalah masalah emosional (27,0%) dan masalah perilaku (24,5%). Tidak ada hubungan antara jenis kelamin dengan kesehatan mental, namun ada hubungan antara tingkat pendidikan responden dengan masalah emosional (p = 0,001) dan total kesulitan (p = 0,002). Dapat didimpulkan bahwa kesehatan mental pada remaja di wilayah kerja Puskesmas Colol berhubungan dengan tingkat pendidikan mereka.Kata kunci: remaja; masalah kesehatan mental; tingkat pendidikan